PENGEMBANGAN KEAHLIAN WIRAUSAHA UNTUK SANTRI PADA PONDOK PESANTREN - Bayu Sudrajat (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
Islamic boarding school is one of the Islamic educational institutions in Indonesia. The reform and reconstruction of the Islamic educational system and its institutions must be carried out, especially in view of the development of the global world, which requires the constant improvement of all Islamic educational institutions. One way to increase the functionality of Islamic boarding schools concerns the financial independence of Islamic boarding schools, especially for students. Because there are still many public perceptions that students in the entrepreneurial world do not have a positive enough image. Another problem is the fate of the santri after their "study" at the Islamic boarding school. Career prospects for them are very slim, especially if they do not have enough formal education. This research is a library research (library research). This study uses the types and sources of secondary data obtained from research results, articles and reference books that discuss topics related to the research theme. This research approach uses a descriptive qualitative approach, which is an effort to understand the various concepts found in the research process, using content analysis techniques (content analysis). The results of the study show that entrepreneurship development can be done anywhere, including in Islamic boarding schools. This entrepreneurial activity is very helpful, improving the economy of the Islamic boarding school. In addition, the existence of this entrepreneurial activity also helps the ability of the students. Because many think that santri are only capable in the religious field, but for fields outside of religion they are not yet capable